Supporting Adoptive Parents: A Study on Personal Self-Care. Issue 2 (3rd April 2019) - Miller, J. Jay; Niu, Chunling; Womack, Rachel; Shalash, Nada
Abstract: This study explored the personal self-care practices of adoptive parents ( N  = 229) in one southeastern state. Overall, findings indicate that adoptive parents only engage in moderate modest self-care practices. Significant differences in self-care practices were detected by health status (self-report) and current financial status . In summary, the healthier one perceived themselves to be and the more financially stable they were, the more they tended to engage in self-care practices. Data suggest the need for entities involved with potential and/or adoptive parents need to explicitly engage adoptive parents in education about self-care and training in support of self-care practices. As well, data indicate the need for reframing self-care from an ancillary activity to an integrated tool to assuage the challenges facing adoptive parents.